Labour market rigidities, financial integration and international risk sharing in the OECD - Jarko Fidrmuc; Neil Foster; Johann Scharler (Center for Economic Studies and ifo Institute (CESifo), 2007)
Economic theory predicts that consumption growth rates should be highly correlated across countries. Empirical evidence overwhelmingly rejects this prediction. We examine whether increased financial integration and labour market rigidities can help explain this apparent contradiction between theory and empirics. Using data for OECD countries we show that although financial integration has a limited impact upon cross-country consumption correlations, labour market rigidities significantly increase consumption correlations. The results suggest that labour market rigidities improve the allocation of consumption risks either by shifting risk from employees to firms and shareholders or because it makes future income streams easier to use as collateral.
Keywords: E32; F15; E21; 330; Gesamtwirtschaftlicher Konsum; Konjunkturzusammenhang; Arbeitsmarktflexibilisierung; Internationaler Finanzmarkt; Marktintegration; Direktinvestition; Schätzung; OECD-Staaten